Stability of tropical forest tree carbon‐water relations in a rainfall exclusion treatment through shifts in effective water uptake depth. (21st September 2021) - Pivovaroff, Alexandria L.; McDowell, Nate G.; Rodrigues, Tayana Barrozo; Brodribb, Tim; Cernusak, Lucas A.; Choat, Brendan; Grossiord, Charlotte; Ishida, Yoko; Jardine, Kolby J.; Laurance, Susan; Leff, Riley; Li, Weibin; et al.
Abstract: Increasing severity and frequency of drought is predicted for large portions of the terrestrial biosphere, with major impacts already documented in wet tropical forests. Using a 4‐year rainfall exclusion experiment in the Daintree Rainforest in northeast Australia, we examined canopy tree responses to reduced precipitation and soil water availability by quantifying seasonal changes in plant hydraulic and carbon traits for 11 tree species between control and drought treatments. Even with reduced soil volumetric water content in the upper 1 m of soil in the drought treatment, we found no significant difference between treatments for predawn and midday leaf water potential, photosynthesis, stomatal conductance, foliar stable carbon isotope composition, leaf mass per area, turgor loss point, xylem vessel anatomy, or leaf and stem nonstructural carbohydrates. While empirical measurements of aboveground traits revealed homeostatic maintenance of plant water status and traits in response to reduced soil moisture, modeled belowground dynamics revealed that trees in the drought treatment shifted the depth from which water was acquired to deeper soil layers. These findings reveal that belowground acclimation of tree water uptake depth may buffer tropical rainforests from more severe droughts that may arise in future with climate change. Abstract : In a rainfall exclusion experiment in the Daintree Rainforest in Australia, tropical canopy trees displayed homeostatic maintenance of aboveground traits in response to reduced soil moisture. This was explained by shifts in belowground dynamics, with trees in the drought treatment having deeper roots to access water in deeper soil layers. These findings reveal that belowground acclimation of tree water uptake depth may buffer tropical rainforests from more severe droughts that may arise in future with climate change.